1997
DOI: 10.1016/s0009-2509(97)00222-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic simulation of gas-liquid two-phase flow: effect of column aspect ratio on the flow structure

Abstract: Abstract--ln this paper an Eulerian/Lagrangian model, describing the hydrodynamics of a gas-liquid bubble column, is presented. The model resolves the time dependent, twodimensional motion of small, spherical gas bubbles in a liquid using the equation of motion. The model incorporates all relevant forces acting on a bubble as it rises through the liquid, and additionally accounts for direct bubble-bubble interactions. The liquid-phase hydrodynamics are described using the volume-averaged Navier-Stokes equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
95
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 12 publications
12
95
1
3
Order By: Relevance
“…In the literature, there is no universal agreement that indicates that the CFD models are capable of predicting the experimental results of multiphase flow regimes [10]. For instance, Delnoij et al [11,12,13] have used Eulerian-Lagrangian approach in 119-2 a flat bubble column to model two-phase flow by using laminar flow model, as well as drag, lift, virtual-mass, and hydrodynamic-interaction forces [14]. Sokolichin and Eigenberger [15] have obtained same results by using finer grid size and neglecting the effects of virtual-mass and lift forces, as well as bubble-bubble interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there is no universal agreement that indicates that the CFD models are capable of predicting the experimental results of multiphase flow regimes [10]. For instance, Delnoij et al [11,12,13] have used Eulerian-Lagrangian approach in 119-2 a flat bubble column to model two-phase flow by using laminar flow model, as well as drag, lift, virtual-mass, and hydrodynamic-interaction forces [14]. Sokolichin and Eigenberger [15] have obtained same results by using finer grid size and neglecting the effects of virtual-mass and lift forces, as well as bubble-bubble interactions.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 There are numerous studies that have applied either the Euler-Euler or the Euler-Lagrange approach within 2D or 3D two-fluid turbulent models. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Large-eddy simulation (LES) studies have also been reported in the literature. 33,34 Additionally, several researchers have reported on the prediction of flow-regime transitions using either numerical simulations 35 or linear stability analysis of various model equations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of bubble columns either employing Eulerian-Eulerian models [ [1][2][3][4][5], Euleri an-Lagrang ian mode ls [6][7][8] , or Volume of Fluid (VOF) [9] methods were surveyed. The Eulerian-Eulerian model treats di spersed (gas bubb les) and continuous (liquid) phases as interpenetrating continua, and describes the motion for gas and liquid phases Ill an Eulenan frame of reference.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] applied an ulen an-LagrangJan method to imula~e detai led bubble-bub ble interacti ons along With interfacial force in the laminar bubb ly flow regJme. Lm et at.…”
Section: Introductionmentioning
confidence: 99%